Front Cover: Miniaturized capillary ion chromatograph with UV light‐emitting diode based indirect absorbance detection for anion analysis in potable and environmental waters. Issue 16 (22nd August 2018) - Murray, Eoin; Li, Yan; Currivan, Sinead A.; Moore, Breda; Morrin, Aoife; Diamond, Dermot; Macka, Mirek; Paull, Brett
Abstract : J Sep Sci 2018, 41, 3224–3231 DOI:10.1002/jssc.201800495 The cover picture shows indirect absorbance detection of small inorganic anions in water achieved using deep UV light emitting diodes (LEDs) within a miniaturised, low‐cost capillary ion chromatography (IC) system. The developed capillary IC system, was assembled on a small footprint modular platform with an interchangeable design, comprised predominantly of off‐the‐shelf miniature and lightweight components. This design approach allowed for a light, flexible and low‐cost system, highlighting the potential of the system for portable or in‐situ water analysis applications in the future.